The Correlation Between Gestational Age and Gingivitis Status Among Pregnant Women at Kras Community Health Center, Kediri Regency - Nasuhan Fachri Imansyah; Sri Hidayati; Agus Marjianto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Gingivitis is one of the most common oral health problems experienced by pregnant women, largely influenced by hormonal fluctuations that occur throughout gestation. These physiological changes increase gingival vascularity, reduce immune response, and heighten sensitivity to plaque accumulation, thereby placing pregnant women at higher risk of developing gingival inflammation. Preliminary data from the Kras Community Health Centre revealed an alarmingly high prevalence of gingivitis, indicating the need for further investigation. This study aimed to analyze the correlation between gestational age and gingivitis status among pregnant women at the Kras Community Health Centre, Kediri Regency. An analytical cross-sectional design was employed involving 75 pregnant women selected through simple random sampling. Gingivitis status was assessed using the Gingival Index, while gestational age was categorized into three trimesters. Data collection was conducted through direct clinical examinations using standardized observation sheets. Spearman’s Rank Correlation Test was used to analyze the association between the two variables. The results showed that most respondents were in the second trimester (45.3%), and the majority presented with moderate gingivitis (62.7%). Statistical analysis demonstrated a significant correlation between gestational age and gingivitis status (ρ = 0.000; α = 0.05), with a strong positive correlation coefficient (r = 0.746). These findings indicate that gingivitis severity tends to increase as pregnancy progresses. In conclusion, gestational age is significantly associated with gingival health status among pregnant women, highlighting the importance of integrating periodontal assessment and oral health education into routine antenatal services to prevent worsening gingival conditions and promote maternal well-being.